Women, Works and Stories: An Analysis of Life Trajectories in a Teuto-Brazilian Community of RS - Tatiana Souza de Camargo; Muriel Closs Boeff (Universidade Federal do Norte do Tocantins, 2018)
This article presents the intersections between two studies conducted in the same municipality of German colonization, located in the Encosta da Serra Gaúcha / RS. Both used ethnographic research tools, such as interviews and participant observation recorded as a field diary, analyzed in a combined manner. The first, held in Women's Groups and with representatives of the Agriculture and Education Sector and the Rural Workers' Union, sought to investigate the generational succession in the family agriculture of the municipality, focusing on young women. The second was carried out in a Family Health Strategy Team, with users diagnosed with depression, trying to understand the experiences and meanings involved in the process of constructing this diagnosis. We consider that the analyzes drawn from these research movements bring valuable contributions so that the community organization is considered, especially in terms of work alternatives and educational strategies in Countryside Education that are capable of promote the generational succession of family agriculture in the municipality and to incorporate the theme of gender, thus generating a real increase in terms of the quality of life of this population.